UTERINE PROLAPSE IN RELATION TO SERUM CALCIUM, MAGNESIUM AND INORGANIC PHOSPHORUS IN AWASSI EWES - F. Majeed, A.; B. Ali, J.; N. Al-Kushal, M. (The Iraqi Journal of Veterinary Medicine, 1989)
The study was undertaken to investigate the relationship between serum calcium, magnesium and inorganic phosphorus in the uterine prolapse in Awassi Ewes. The serum of animals with uterine prolapse had significantly lower calcium and inorganic phosphorus levels (P<0.01) as compared to the control group, While serum magnesium showed no significance (P<0.05) difference. The results of this study revealed the importance of application of drugs rich in minerals espacially calcium in treating the condition.